2023
DOI: 10.3389/fendo.2023.1181538
|View full text |Cite
|
Sign up to set email alerts
|

High-dimensional single-cell analysis unveils distinct immune signatures of peripheral blood in patients with pancreatic ductal adenocarcinoma

Abstract: IntroductionPancreatic ductal adenocarcinoma (PDAC) is one of the most lethal malignancies with poor response to immune checkpoint inhibitors. The mechanism of such poor response is not completely understood.MethodsWe assessed T-cell receptor (TCR) repertoire and RNA expression at the single-cell level using high-dimensional sequencing of peripheral blood immune cells isolated from PDAC patients and from healthy human controls. We validated RNA-sequencing data by performing mass cytometry (CyTOF) and by measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
0
0
Order By: Relevance
“…However, contrasting with the findings in HCC, Cui et al ( 28 ) reported that the diversity of the circulating TCR repertoire in patients with cervical cancer (CC) was lower than that in healthy women and gradually decreased during tumor development. Similarly, the TCR repertoire diversity in the peripheral blood of patients with pancreatic ductal adenocarcinoma (PDAC) was shown to decline compared with that in healthy controls in a study performed by Pan et al ( 29 ) involving analysis of the inverse Simpson diversity index. The authors speculated that the reduced TCR repertoire diversity may be caused by the proliferation of CD8 + T cells.…”
Section: Application Of Tcrs In Tumor Diagnosismentioning
confidence: 99%
“…However, contrasting with the findings in HCC, Cui et al ( 28 ) reported that the diversity of the circulating TCR repertoire in patients with cervical cancer (CC) was lower than that in healthy women and gradually decreased during tumor development. Similarly, the TCR repertoire diversity in the peripheral blood of patients with pancreatic ductal adenocarcinoma (PDAC) was shown to decline compared with that in healthy controls in a study performed by Pan et al ( 29 ) involving analysis of the inverse Simpson diversity index. The authors speculated that the reduced TCR repertoire diversity may be caused by the proliferation of CD8 + T cells.…”
Section: Application Of Tcrs In Tumor Diagnosismentioning
confidence: 99%